Developing a Framework of Deviant Behaviors of Physical Education Teachers - Turkmani, Ehsan Mohamadi; Naghi-Pour Givi, Behnam; Monazami, Amir Hosein (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to develop a framework of deviant behaviors of P.E. teachers by qualitative methods. For this purpose, depth interviews were conducted with 18 experts consisting of school principals, retired P.E. teachers, inspectors of the education department, and teachers of other subjects. Directed content analysis technique is used for analyzing data. We generated 40 codes categorized in 25 sub themes, 10 themes, and four dimensions. TheP.E. teachers’ deviant behaviors dimension was professional commitment deviance, property deviance, personal deviance and political deviance. Furthermore, we separated P.E. teachers’ deviant behaviors into three groups based on victims or targets. These three groups included pupils, schools and colleagues. The results of the study, despite the similarity to popular typologies of deviant behavior, showed a number of new deviant behaviors which are specific forP.E. teachers. The findings can be used for choosing appropriate corrective actions for P.E. teachers’ deviant behaviors.